Pelatihan Pembuatan Kemasan (Packaging) untuk Meningkatkan Pemasaran Produk UMKM di Kota Tegal - Nugroho Adhi Santoso; Zainul Arif; Gunawan Gunawan; Anik Mutaqin; Fikri Zain Hidayatullah (Gapenas Publisher, 2022)
In order to realize the characteristics of STMIK YMI TEGAL as a place for the formation of independent Bachelors and Bachelors and to realize the Vision and Mission of STMIK YMI TEGAL in terms of Independence and Entrepreneurship, the Center for Entrepreneurship, Independence and Incubator Institute for Research and Community Service (LPPM) synergizes the LPPM Entrepreneurship Development Program with various parties, including: Micro, Small and Medium Enterprises (UMKM) Tegal City. As a form of synergy, LPPM STMIK YMI TEGAL in collaboration with the National Madani Capital (PNM) held Product Packaging Design Training, in order to provide skills for the community through Tegal City SMEs